THEORETICAL FOUNDATIONS OF THE INTERRELATION BETWEEN THE CREATION OF AN ECOLOGICAL NETWORK AND LAND MANAGEMENT - Styranivskyi , Б. (Bulletin of Lviv National Environmental University. Series «Architecture and Construction», 2025)
The article presents the concept of creating an ecological network as the most effective approach to preventing habitat fragmentation and minimizing the impact of human activity on the environment. It emphasizes the necessity of taking into account biodiversity needs, wild nature, and the vital ecological connections in the planning and management of land use. The ecological network concept entails identifying valuable natural areas and connecting them with ecological corridors, integrating the structural components of the ecological network into planning and project documentation for land management. The study highlights two key directions of land-use planning for the purposes of ecological network design: improving the existing state of natural ecosystems and their biodiversity through changes in land use; and creating a new spatial organization and related infrastructure, considering the needs of socioeconomic development and biodiversity protection. The process of creating the ecological network includes stages such as goal setting, planning, design, management, and monitoring, applying an interdisciplinary approach and public participation. Important tools for formulating the ecological network are strategic environmental assessment and the integration of measures into regional and local land-management documentation. This process involves identifying ecosystem resilience problems, a stakeholders’ participation procedure, and assessment of environmental impacts during the design and implementation of measures. The study underscores the importance of increasing attention to biodiversity in Ukraine, the need to develop effective mechanisms for implementing measures to create key and connecting territories to improve ecological connectivity. Further research will focus on addressing practical aspects of land management in the context of ecological network creation.